Prediction of outdoor and indoor ventilation of high-rise building neighborhoods based on flow and turbulence around buildings - Pan, Shanshan (2015)
The global trend of urbanization has led to the increasing concern of the urban environment. Urban airflow which is directly related to pollutant dispersion and natural ventilation has attracted considerable amount of research interests. This thesis focuses on the airflow around high-rise building neighborhoods, based on which the outdoor and the indoor ventilation potentials are predicted. A field measurement campaign was carried out in a high-rise residential building neighborhood in Singapore in the northeast and the southwest monsoon seasons. Ten integrated weather stations were installed at the pedestrian level and in the buildings to measure wind speed, wind direction and temperature. Reference wind speeds at the roof and at the airport were also measured. In general, strong mixing seems to exist in the neighborhood. It is found that the pedestrian level wind speed in the neighborhood is relatively uniform, being about 40% of the wind speed at the roof, when the angle of attack of the incident wind is less than 60. The vertical wind profiles in the downwind buildings also vary little with height. In addition, the in-canopy turbulence also shows high spatial and temporal uniformity when normalized with the roof turbulence velocity. For the neighborhood studied, the outdoor ventilation potential is equivalent to the amount of the airflow available within the neighborhood when the ambient flow condition is given. Hence, the wind speeds at the pedestrian level and in the buildings over height are converted to fractions of the airport wind speed and compared between the two monsoon seasons. It is found that this neighborhood is in the advantageous condition during the northeast monsoon because of the low upwind obstruction. Two types of the indoor ventilation are covered, cross ventilation and single-sided ventilation. Relatively good agreement is found between the measured cross-ventilation velocity in the neighborhood and the calculated velocity from the wind pressure coefficient. CFD simulations were performed on the single-sided ventilation to investigate the effect of turbulence intensity. The results suggest that the air change rate increases with increasing turbulence intensity when the window is on the windward or side walls.